Social equality and Christian life in Paul's first letter to the Corinthians - M. Tilly (Acta Theologica)
This contribution seeks to clarify how the category of eschatological equality in 1 Corinthians is to be ascertained. Is equality, in this instance, to be understood as the annulment of status differences within the Christian congregation, or does it belong to an eschatological plan of an ideal or utopic world? Is the new Christian existence of the Corinthians conceived as real, as outwardly visible or as socially perceivable? This study is aimed at understanding the theological construction connected with these questions by interpreting the paradigmatic relation of the status-designating pairs ???????? and ???????; ????????? and ??????; ????????/????, and ???? (or ????? and ????) within the Pauline argument.